Voluntary standards and certification for environmentally and social ly responsible agricultural production and trade - Liu, Pascal; Andersen, Mikkel; Pazderka, Catherine; Food and Agriculture Organization of the United Nations. Commodit ies and Trade Division; FAO Meeting on Voluntary Standards and Certification for Environment ally and Socially Responsible Agricultural Production and Trade (200 4 : Rome, Italy) (Rome : Commodities and Trade Dvision, Food and Agriculture Organi zation of the United Nations, 2004)
This publication is a summary of the presentations and discussions t hat took place during the meeting on "Voluntary Standards and Certifica tion for Responsible Agricultural Production and Trade" organized by FA O in April 2004. It presents the situation of the main import markets f or certified products and the evolution of demand. Case studies aimed a t comparing sustainable farming methods with conventional methods are p resented. These comparisons focus on production cost, yield, price prem ium and net profit. The difficulties with which the producers are confr onted are analysed and possible solutions to overcome them are explored . The publication also discusses the roles of nongovernmental organizat ions, private stakeholders and other institutions involved in sustainab le agriculture and explores possibilities for greater collaboration amo ng them.
Benefits of certification: does certification benefit farmers and so ciety as a whole? -- Overcoming the constraints of certification: facil itating certification through NGO initiatives -- Building alliances to expand market opportunities for responsible production.
Includes bibliographical references.
Keywords: Farm produce -- Certification -- Congresses; Environmental responsibility -- Congresses. -- Congresses; Sustainable agriculture